2017
DOI: 10.1080/00015385.2017.1306309
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylated haemoglobin and coronary atherosclerosis in non-diabetic patients: is it a prognostic factor?

Abstract: The present study demonstrated that HbA1c might be an independent diagnostic factor in non-diabetic patients with severe coronary atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Some previous studies have shown consistent results with ours investigating correlation between HbA1c and CACS progression or coronary atherosclerosis. Reza Ajudani, in a cross-sectional study based on 411 patients without history of known diabetes mellitus, reported that HbA1c may be functioning as an independent diagnostic factor in nondiabetic patients with severe coronary atherosclerosis [27]. Besides, Wenhui Zhao et al used African American and white diabetic patients as the study population and obtained similar results [28].…”
Section: Discussionmentioning
confidence: 83%
“…Some previous studies have shown consistent results with ours investigating correlation between HbA1c and CACS progression or coronary atherosclerosis. Reza Ajudani, in a cross-sectional study based on 411 patients without history of known diabetes mellitus, reported that HbA1c may be functioning as an independent diagnostic factor in nondiabetic patients with severe coronary atherosclerosis [27]. Besides, Wenhui Zhao et al used African American and white diabetic patients as the study population and obtained similar results [28].…”
Section: Discussionmentioning
confidence: 83%
“…Some previous studies have shown the consistent results with ours investigating correlation between HbA1c and coronary artery calcium score progression or coronary atherosclerosis. Based on 411 patients without history of known diabetes mellitus, Reza Ajudani reported that HbA1c may be an independent diagnostic factor in non-diabetic patients with severe coronary atherosclerosis in a cross-sectional study [19]. Besides, Wenhui Zhao et al used African American and white diabetic patients as the study population and obtained similar results [20].…”
Section: Discussionmentioning
confidence: 86%
“…First, the sample size of this study was relatively large. Seconde, previous articles that also studied HbA1c and coronary artery calcium score or coronary atherosclerosis did not clarify the nonlinear relationship [19,20,[24][25][26][27][28][29]. To the best of our knowledge, this is the rst time that a non-linear relationship has been reported and an in ection point has been determined and explained in exploring the correlation between HbA1c and coronary artery calcium score progression.…”
Section: Discussionmentioning
confidence: 88%
“…The ideal cut-off value of HbA1c for the formation of coronary artery disease was found to be 5.6% (sensitivity: 60.5%, speci city: 52%) (13). In a study with 411 patients in recent years, based on the ROC curve, the cut-off value of HbA1c between patients with and without coronary atherosclerosis was found to be 5.45% (82.8% sensitivity and 62.7% speci city) (14). In our study, ROC analysis was used and HbA1c cut-off value was 91.55% sensitivity and 61.39% speci city was 5.6% in determining atherosclerotic patients.…”
Section: Discussionmentioning
confidence: 99%